Pb-isotope ratios and the petrogenesis of the Tunkillia Suite, Gawler Craton. Issue 8 (17th November 2021) - Chapman, N. D.; Meffre, S. J.; Maas, R.; Ehrig, K.
Abstract: In situ Pb-isotope ratios of alkali feldspars from laser ablation ICP-MS (LA-ICP-MS) were used to constrain melt-sources of the ca 1690–1670 Ma Tunkillia Suite, an important suite of intrusive rocks located in the Archean–Mesoproterozoic Gawler Craton, South Australia. Tunkillia Suite magmatism has been variously attributed to either a supra-subduction or post-collisional setting. A robust interpretation of the Tunkillia Suite's tectonic setting is important for models of the Proterozoic evolution of the Gawler Craton and Australian continent. The Pb-isotopic results indicate a regional variation involving at least two crustal Pb components corresponding to an ancient, U-depleted reservoir in the western Tunkillia Suite and another that reflects mantle–crustal hybridisation. Inheritance of unradiogenic Pb-isotope ratios seen in the western Tunkillia Suite ( 206 Pb/ 204 Pb = 15.060–15.785, 207 Pb/ 204 Pb = 15.154–15.426, 208 Pb/ 204 Pb = 34.963–35.766) are a globally rare phenomenon that are linked to inheritance from U/Pb-depleted granulites. Pb-isotopic reservoirs containing unradiogenic Pb are among the least melt-fertile sources and are inconsistent with granites generated during continent–continent collision. In contrast, the eastern Tunkillia Suite displays Pb-isotope ratios indicative of crust–mantle mixing, with a volumetrically dominant mantle component ( 206 Pb/ 204 Pb = 15.945–16.143, 207 Pb/ 204 Pb = 15.325–15.414, 208 Pb/ 204 Pb = 35.330–35.757). These values are consistent with published εNd(1680 Ma) (+2.6 to −2.1) and εHf(1680 Ma) (+5.9 to +0.7) signatures that confirm the role of mantle-melts in the petrogenesis of the Tunkillia Suite. The radiogenic isotopic signatures of the Tunkillia Suite contrast with the syn-collisional granitoids generated from crustal anatexis during the 1730–1700 Ma Kimban Orogeny (εNd(t) −11.7 to −0.7) and are consistent with the arc-related ca 1630 Ma St Peters Suite granitoids (εNd(t) +2.31 to −3.46). In addition, isotopic arrays for the Tunkillia Suite demonstrate a similar mixing phenomenon involved in continental arc magmatism of the Andean Cordillera. We contend that the Tunkillia Suite magmatic event is characterised by widespread crustal–mantle hybridisation, favouring a continental arc-like setting. KEY POINTS: Pb- and Nd-isotopic similarities of Tunkillia Suite to modern continental arc magmas. The Tunkillia Suite has geochemical similarities to modern continental arc magmas. Inheritance of unradiogenic Pb-isotopic signatures in the Tunkillia Suite require mafic melt hybridisation. The Tunkillia Suite should be reconsidered to reflect the onset of late Paleoproterozoic subduction-related tectonism in the Gawler Craton.